2016
DOI: 10.1002/mrm.26311
|View full text |Cite
|
Sign up to set email alerts
|

Empirical model of human blood transverse relaxation at 3 T improves MRI T2oximetry

Abstract: Purpose We sought a human blood T2-oximetery calibration curve over the wide range of hematocrits commonly found in anemic patients applicable with T2 Relaxation Under Spin Tagging (TRUST). Methods Blood was drawn from 5 healthy control subjects. Ninety-three in vitro blood transverse relaxation (T2b) measurements were performed at 37° C over a broad range of hematocrits (10–55%) and oxygen saturations (14–100%) at 3T. In vivo TRUST was performed on 35 healthy African American control subjects and 11 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(114 citation statements)
references
References 34 publications
3
108
3
Order By: Relevance
“…The remaining CPMG T 2 preparation sequence parameters included a repetition time of 1978 ms, 110 cm FOV, 5‐mm slice thickness and in plane resolution of 1.7 mm. These modifications did not alter the fundamental measured T 2b .…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…The remaining CPMG T 2 preparation sequence parameters included a repetition time of 1978 ms, 110 cm FOV, 5‐mm slice thickness and in plane resolution of 1.7 mm. These modifications did not alter the fundamental measured T 2b .…”
Section: Methodsmentioning
confidence: 88%
“…Following completion of the ex vivo T 2b measurements, T 2b was derived by applying monoexponential fitting to the blood pool signal and the values were fit to a bilinear relationship of hematocrit (Hct) and oxygen saturation (Y) as follows: 1T2b=A1Hct(1Y)2+A2(1Y)2+A3Hct+A4 where A 1 , A 2, A 3 , and A 4 are empirically determined coefficients .…”
Section: Methodsmentioning
confidence: 99%
“…Numerical simulations revealed that velocity and B1 + strength were the strongest contributors to diminished labeling efficiency and resultant errors between PCASL and PC CBF measurements. At typical carotid velocities and oxygen saturations, differences in T 2 values for healthy and anemic subjects (200ms-300ms) contributed <1.5% to labeling efficiency(10). …”
Section: Resultsmentioning
confidence: 99%
“…The model parameters used were chosen similar to arterial human blood including T 2 = 200ms(10), T 1 = 1600ms(9). Numerical simulations were performed on resonance, in the rotating frame with a numerical step size of 3.6 μs.…”
Section: In Vivo Imagingmentioning
confidence: 99%
See 1 more Smart Citation